Representasi Dampak Psikologis Korban Kekerasan dalam Rumah Tangga pada Film Paranoia (Analisis Semiotika Roland Barthes) - Rosdiana, Anggita Cahya; Susanti, Dwi; Dwihantoro, Prihatin (Universitas Muhammadiyah Magelang, 2024)
Domestik violence remains a critical yet often hidden social issue with profound psychological impacts on victims. This study analyzes the 2021 Indonesian film Paranoia directed by Riri Riza to explore representations of domestic violence and its psychological consequences. Employing a descriptive qualitative method and Roland Barthes’ Semiotic Theory, the research examines denotative, connotative, and mythical meanings in selected scenes. The findings reveal symptoms such as emotional instability, anxiety, and recurring trauma, often triggered by interactions related to the perpetrator. Physical signs, such as cigarette burns, serve as symbolic representations of deeper psychological scars. The film also portrays the effects of trauma on family dynamics, particularly through overprotective behaviors. Ultimately, Paranoia demonstrates the power of film in raising awareness and encouraging social reflection on domestic violence.